Exogenous Application of Citric Acid Ameliorates the Adverse Effect of Heat Stress in Tall Fescue (Lolium arundinaceum) - Hu, Longxing; Zhang, Zhifei; Xiang, Zuoxiang; Yang, Zhijian (Frontiers in Plant Science, 2016)
Citric acid may be involved in plant response to high temperature. The objective of this study was to investigate whether exogenous citric acid could improve heat tolerance in a cool‐season turfgrass species, tall fescue (Lolium arundinaceum), and to determine the physiological mechanisms of citric acid effects on heat stress tolerance. The grasses were subjected to four citric acid levels (0, 0.2, 2 and 20 mM) and two temperature levels (25/20 and 35/30 ± 0.5 ̊C, day/night) treatments in growth chambers. Heat stress increased an electrolyte leakage (EL) and malonaldehyde (MDA) content, while reduced plant growth, chlorophyll (Chl) content, photochemical efficiency (Fv/Fm), root activity and antioxidant enzyme activities (superoxide dismutase, SOD; catalase, CAT; peroxidase, POD). External citric acid alleviated the detrimental effects of heat stress on tall fescue, which was evidenced by decreased EL and MDA content, and improved plant growth under stress conditions. Additionally, the reduction in Chl content, Fv/Fm, SOD, POD, CAT and root activity were ameliorated in citric acid treated plants under heat stressed conditions. High temperature induced the expression of heat shock protein (HSP) genes, which exhibited greater expression levels after citric acid treatment under heat stress. These results suggest that exogenous citric acid application may alleviate growth and physiological damage caused by high temperature. In addition, the exogenously applied citric acid might be responsible for maintaining membrane stability, root activity, and activation of antioxidant response and HSP genes which could contribute to the protective roles of citric acid in tall fescue responses to heat stress.